Analisis Penentuan Beban Pokok Produksi Pada Usaha Tempe Sumber Mas Jember - Luqman Arif Baihaqi; Imam Mas'ud; Yosefa Sayekti (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This study aims to find out the system of business cost control of Tempe Sumber Mas. A Controling based difference between the calculation of the cost of production with cost of production of tempe using full costing. and This research uses Descriptive by Source and Technique Triangulation. The results of this study indicate that the cost control system used by the company is still simple and the calculation of the cost of production of tempe using full costing method is greater than calculate the total production cost used in the tempe production process. Keywords: Expense, Cost of Production, Full Costing, Cost Control